Finansy SSSR otrazhayut tvorcheskiy pod'yem trudyashchikhsya mass! - Kaaban, V. M
Illustrations of industry, masses, and bar graphs Original title: Финансы CCCP отражают творческий подъем трудящихся масс! Suggested translation: USSR finances reflect the creative rise of the working masses! PO-2507